The unmaking of a college : the story of a movement [videorecording (DVD)] - Goldstein, Amy (Amy Barbara); Larson, Nathan, 1970-; Kane, Nicholas Lattimore; Becerra, Marlon; Berman, Joshua; Burns, Ken, 1953- (Kino Lorber, 2022)
It tells the story of the attempted takedown of one of America's most iconoclastic colleges, Hampshire College, how a group of determined students succeeded to save it, and by the same token, save their rights to an education that taught them to think critically and to expect a seat at the table. With the help of the students who filmed their 75-day sit-in (the longest in American college history), director Amy Goldstein builds a thriller-like story weaving interviews with professors, whistleblowers, students, and alumni including filmmaker Ken Burns. A raucous ode to democracy in action, the documentary reflects more broadly on a crisis in higher education and asks: what is the purpose of a college education? Can the storied tradition of the liberal arts and the nation it has created be saved?